CFD modelling of marine discharge mixing and dispersion. Issue 2 (2nd July 2016) - Robinson, David; Wood, Matthew; Piggott, Matthew; Gorman, Gerard
Abstract : Many municipal and industrial outfalls release effluent into water bodies. Temperatures and/or salinities of the effluent and receiving water may be different, and other dissolved/suspended constituents may be present. Away from the outfall, mixing processes usually reduce constituent concentrations to acceptable levels for local water quality. However, at the outlet, concentrations may be sufficient to cause environmental concern. Accurate dispersion prediction is therefore important. Two-stage modelling approaches are typically used: (1) a near-field dilution assessment, based on mixing zone or empirical models; and (2) a mid- /far-field dispersion assessment, using hydrodynamic models. As computational and numerical methods improve, computational fluid dynamics (CFD) can increasingly model dispersion across both regions. These methods require validation of the underlying discretisation and turbulence schemes. Preliminary validation is presented for near-field simulations of buoyant and dense jets. Buoyant jet predictions compare well with established results. Preliminary simulations under-predict entrainment into the dense jet, overly-predicting near-field concentrations.